Organizacje społeczne wsi Czerniewice (pow. Tomaszów Mazowiecki) - Domańska, Aneta (Zeszyty Wiejskie, 2013)
Czerniewice is the side of action of socio-political, educational, youth, sports, social and economic, co-operative, Church organisations. The diversity of organizations affect social and cultural transformation, shape the knowledge and awareness of the inhabitants. A good relationship between existing organizations strengthen the comprehensive of village activity. The role of activists leading social organizations should be emphasized. Much depends on their commitment, talents, interests, activities and a passion for social work. They must thoroughly know their environment: the needs, ambitions, aspirations of the population. Belief in sense and conviction of the rightness of the business helps them to overcome the difficulties that appear on the way of organizing attractive initiatives and projects.